IMMU-09. MODULATING THE MYELOID POPULATION IN DIPG MODELS WITH ONCOLYTIC VIRUS AND COMPLEMENT INHIBITORS SHOWS THERAPEUTIC EFFICACY - Puigdelloses, Montserrat (Neuro Oncol, 2021)
Diffuse intrinsic pontine glioma (DIPG) is the leading cause of brain tumor-related death in children. It is characterised for having a non-inflammatory microenvironment and be immunologically inert. Therefore, strategies aiming to break the microenvironment status-quo in this disease could provide therapeutic benefit. The complement system promotes tumor progression due to the continuous production of anaphylatoxins leading to the infiltration of myeloid cells, which express high levels of complement receptors (C3aR and C5aR1). We have in silico data showing the high expression of C5aR1 in DIPGs. Thus, we wanted to assess first whether complement C5aR1 could constitute an actionable target, and second whether combining C5aR1 inhibitors with oncolytic virus could result in a superior antitumor immune response than either agent alone in DIPG. In this study, we used two different peptide inhibitors of C5aR1, PMX53 and PMX205 combined with the virus Delta-24-ACT (an oncolytic virus armed with 4-1BBL). We performed in vivo studies to evaluate the efficacy of this combination in immunocompetent DIPG models. Our data showed that the combination Delta-24-ACT/PMX53 significantly extended the median survival of the animals when compared with either agent alone, and led to long-term survivors that generated immune memory. The combination treatment modulated the tumor microenvironment promoting an increase in lymphocytes, mainly CD8+ cells presenting an active phenotype, and a reduction in C5aR1 expression in the myeloid compartment. We are currently evaluating in vivo whether PMX205, which has an improved ability to cross the blood brain barrier, leads to better therapeutic response. In summary, the combination of Delta-24-ACT with a C5aR1 inhibitor showed the capacity to shake the DIPG tumor microenvironment and unleashed an antitumor immune response. These data underscore the possibilities to combine oncolytic virus with targets of the tumor microenvironment to improve their therapeutic benefit in DIPGs.